Sistem Pendukung Keputusan Pemilihan Alat Kontrasepsi pada Wanita Menggunakan Metode Weighted Product (Wp) - Miftahul Jannah; Achmad Sarwandianto; Lusi Ariyani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Decision Support System for Selecting Contraceptives for Women Using the Weighted Product (WP) Method to determine the best alternative results. In this method, there are 5 (five) criteria and 5 alternative contraceptives for women. To test the results, a comparison is made of the results given by the midwife with the results from the system. After that, ranking is carried out according to the highest value from the calculation results for selecting contraceptives for women.